FASHION SEBAGAI KOMUNIKASI IDENTITAS SOSIAL MAHASISWA FKIP UNS - Firdaus, Ghani (ISSN.2252-8407)
ABSTRACT Ghani Firdaus. K8412032. FASHION AS SOCIAL IDENTITY OF STUDENTS OF FKIP UNS. Essay. Surakarta: the Faculty of Education. March Surakarta University, November 2016.This research aimed to identified factors underlying students of FKIP UNS in used the fashion when studying, and described strategy of FKIP students in used the fashion when studying.This research used descriptive-qualitative approaches with case study. The objects of this research is all the students of FKIP UNS. Data were gained from informant. Making the subject of research with purposive sampling. In collecting data using direct observation and structured interviews. Triangulation data used to test the validity of the data. The technique of data analysis used interactive analysis model.The results of this research showed (1) the factors underlying students of FKIP UNS in used the fashion when studying are: a) the recategorization was less going well; b) the recategorization was strong to others identity; c) fashion as artifactual?s communication of students of FKIP UNS. (2) Strategy of students in used the fashion when studying is crossing category. The truth is individual may have more than one identity, with the result that crossing category are consequence of double identity. When students was studying and used the uniforms that combined their fashion. However, the uniforms and fashion have differential identity, this is crossing category in the context of social identity communication in the fashion.Based on the results, it can be concluded that the use of fashion on students of FKIP UNS when studying is a manifestation of sosial identity. Besides uniforms, students also have another identity that they show in the same time when studying, that is fashion. Keywords : fashion, communication, social identity